REVIEW ARTIKEL : POTENSI LIMBAH KULIT NANAS (ANANAS COMOSUS L. MERR) SEBAGAI SHAMPO ANTIKETOMBE - Agustina, Putri; Budiyanti, Lia Eka (Politeknik Tiara Bunda, 2023)
Shampoo is one of the cosmetics used on hair to treat various problems, one of which is dandruff. Dandruff is the excessive release of dead skin cells on the head which can be accompanied by itching and inflammation of the scalp. Pineapple skin is part of the pineapple that is usually not used and will become waste. The purpose of reviewing this article is to provide information to readers regarding the potential of pineapple peel as an anti-dandruff shampoo. The method used in this research is Literature Review Article by taking literature from Google Scholar, Researchgate and PubMed. Based on the results of the review article, it was found that pineapple peel has the potential as an anti-dandruff shampoo against Candida albicans, Pityrosporum ovale, Trichophyton mentaghrophytes and Malassezia furfur. At a concentration of 25%, pineapple peel extract had an inhibition of 22,73 mm against Trichophyton mentaghrophytes and 24,16 mm against Malassezia furfur.